The effect of Skin Factor On Water Injectivity during WAG process - Hamid, Mohamed Ali (2010)
Potential loss of injectivity and corresponding loss of reservoir pressure and possibly loss of miscibility resulting in lower oil recovery has potentially major impact on the economics of WAG processes. Additionally there is a question always if the near wellbore phenomena such as skin affect the injectivity or just in-depth phenomenon does. In this paper the effect of the skin factor on water injectivity during WAG process was studied. Water injectivity model has been derived starting from the continuity equation, Corey’s model and Taylor’s series, with assumptions of constant injection rate, three banks (Water, gas and water flooded oil) composite reservoir, constant thickness, constant pressure at the outer boundary, the saturations within each bank are assumed to be constant. Then we studied the effect of skin factor on injectivity. As the damage increases (increasing of S) the injectivity decreases, and the more impact appears at small damage values (between -1to 6 for S value).